1975
DOI: 10.1093/jaoac/58.5.902
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Bioavailability of Iron

Abstract: Eight laboratories conducted a test for the estimation of the bioavailability of iron from 4 sources, using depleted male albino rats. Ferrous sulfate was used as the reference standard. Ferric orthophosphate was found to have a relative biological value of 11 (range 6–22), an old sample of hydrogen-reduced iron 27 (range 15–41), and ferric citrate 96 (range 75–125). Good results were obtained with a simplified basal diet prepared without ingredients that had previously contributed variable quantities of iron.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Iron requirement studies on Atlantic salmon have shown that both hepatic iron and blood haemoglobin concentrations respond to variation in dietary iron concentration (Bjørnevik & Maage 1993;Andersen et al 1996). Blood haemoglobin concentration and hepatic iron concentration have both been used as criteria for evaluating iron bioavailability in studies performed on mammals (Fritz et al 1975;Ricketts & Kies 1994) and fish (Ukawa et al 1994). To establish iron bioavailability, it is recommended to keep the dietary concentration below the requirement in order to give maximal response when the nutrient is fed (Fox et al 1981;Mutanen 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron requirement studies on Atlantic salmon have shown that both hepatic iron and blood haemoglobin concentrations respond to variation in dietary iron concentration (Bjørnevik & Maage 1993;Andersen et al 1996). Blood haemoglobin concentration and hepatic iron concentration have both been used as criteria for evaluating iron bioavailability in studies performed on mammals (Fritz et al 1975;Ricketts & Kies 1994) and fish (Ukawa et al 1994). To establish iron bioavailability, it is recommended to keep the dietary concentration below the requirement in order to give maximal response when the nutrient is fed (Fox et al 1981;Mutanen 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Bioavailability of different iron compounds should therefore be tested relative to a reference compound with a high bioavailability. This has usually been iron(II)sulphate (Fritz et al 1975;Soevik et al 1979;Hettiarachchy & Erdman 1984). In the present experiment, bioavailability was assessed by hepatic iron and blood haemoglobin concentrations, using the slope ratio method with iron(II)sulphate as the reference (Fox et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the methodologies used to determine the bioavailability of iron from beef were different from those used for soybean protein preparations. Furthermore, the methods used to determine bioavailability in these foods are different from the procedure which is currently being recommended as the official method for determining iron bioavailability (Fritz et al, 1975). The objectives of this study were to use the same method to compare the bioavailabilities of these two food sources of iron in rats and to evaluate various methods of determining and calculating iron availability from foods.…”
mentioning
confidence: 99%
“…The objectives of this study were to use the same method to compare the bioavailabilities of these two food sources of iron in rats and to evaluate various methods of determining and calculating iron availability from foods. Fritz et al (1975) have recommended that their method be adopted as the official method for determining iron bioavailability. Although this method can yield acceptable results, there are some potential problems with it.…”
mentioning
confidence: 99%
See 1 more Smart Citation